Adsorptive environmental applications of MXene nanomaterials: a review. Issue 36 (30th May 2018) - Zhang, Yujuan; Wang, Lin; Zhang, Ningning; Zhou, Zhangjian
Abstract : Due to their large specific surface area and abundant active surficial sites, MXenes can adsorb various environmental pollutants. Abstract : Since titanium carbide Ti3 C2 nanosheets were first produced in 2011, an increasing number of members of this new family of two-dimensional transition metal carbides/nitride (MXene) materials have been successfully synthesized. Due to their large specific surface area, hydrophilic nature and abundant highly active surface sites, MXenes have been demonstrated to adsorb a variety of environmental pollutants, including heavy metal ions, organic dyes, radionuclides, and gas molecules, and thus can be used for the removal of pollutants and even sensing. In this review, we summarize the recent research progress on MXene materials in the adsorptive remediation of environmental pollutants and highlight the main challenges in the future to understand the full potential of MXene materials in environmental systems.